Respostas
respondido por:
0
2x²-8x+14x-56=0
2x²+6x-56=0
Delta: 6² - 4x2x(-56)
delta = 36+ 448
delta= 484
raiz= 22.
x1 = -6+22/4= 4
x2= -6-22/4= - 7
2x²+6x-56=0
Delta: 6² - 4x2x(-56)
delta = 36+ 448
delta= 484
raiz= 22.
x1 = -6+22/4= 4
x2= -6-22/4= - 7
respondido por:
1
Olá Teuzinho,
Como vai?
Vamos lá,
(x + 7) * (2x - 8) = 0
2x² - 8x + 14x - 56 = 0
2x² + 6x - 56 = 0
Δ = 6² - 4 * 2 * (-56)
Δ = 36 + 448
Δ = 484
Como vai?
Vamos lá,
(x + 7) * (2x - 8) = 0
2x² - 8x + 14x - 56 = 0
2x² + 6x - 56 = 0
Δ = 6² - 4 * 2 * (-56)
Δ = 36 + 448
Δ = 484
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás